2016
DOI: 10.1016/j.envint.2015.10.017
|View full text |Cite
|
Sign up to set email alerts
|

Elevated childhood exposure to arsenic despite reduced drinking water concentrations — A longitudinal cohort study in rural Bangladesh

Abstract: Despite decreased water arsenic concentrations in rural Bangladesh, the children still have elevated exposure, largely from food. Considering the known risks of severe health effects in children, additional mitigation strategies are needed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
30
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 73 publications
(31 citation statements)
references
References 51 publications
1
30
0
Order By: Relevance
“…A great amount of arsenic is removed during the rice polishing [ 21 , 50 52 ]. Besides, variation in the arsenic concentration may occur due to different cultivars, geography, environment, water quality, and growth conditions [ 21 , 24 , 25 , 29 , 30 , 37 , 51 , 53 56 ].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A great amount of arsenic is removed during the rice polishing [ 21 , 50 52 ]. Besides, variation in the arsenic concentration may occur due to different cultivars, geography, environment, water quality, and growth conditions [ 21 , 24 , 25 , 29 , 30 , 37 , 51 , 53 56 ].…”
Section: Resultsmentioning
confidence: 99%
“…The results found in this study on the total arsenic contents were also in agreement with those previously reported for rice analyzed in other countries ( Table 7 ). The exception is for arsenic concentration found in rice cultivated in Bangladesh, one of the countries that have been mostly vulnerable to arsenic exposure, causing a serious Public Health problem [ 33 , 34 , 53 ]. In the 1970s, the plumbing pipes contaminated by arsenic were installed in the country, and it caused the contamination of the water consumed by the population.…”
Section: Resultsmentioning
confidence: 99%
“…Exposures to arsenic and manganese among infants and mothers often occur via additional dietary sources outside of drinking water, so our reliance on this metric likely means we underestimated the true exposure levels. However, contaminated drinking water is the primary source of elevated exposures to arsenic and manganese in Bangladesh [84,96]. Breastfeeding can reduce postnatal exposures, as arsenic and manganese are not fat soluble and typically not found in high concentrations in breast milk [47,48].…”
Section: Discussionmentioning
confidence: 99%
“…Apart from occupational exposure, one of the most important environmental routes of exposure is drinking As‐contaminated water. Based on arsenic permissible limits 0.01 mg L −1 , several countries are still confronted with challenge and health risk, including China, 1 Bangladesh, 2 Argentina, 3 India, 4 Vietnam, 5,6 and the United States 7 . The other major source is As‐contaminated air and food caused by combustion high As‐containing coal in unventilated indoor stoves for cooking, which has been exclusively reported in Guizhou province in China in 2002 year 8 .…”
Section: Introductionmentioning
confidence: 99%